A study of the psycho, social, & economic impact of a US Habitat for Humanity affiliate. Issue 1 (16th March 2015) - Eriks, Christine; Decker, Phillip J; Ainsworth, Natalie; Ward, Rachel; Durand, Roger; Mitchell, Jordan; Beck, Courtney
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to inform funders and potential funders alike of the likely outcomes of their financial contributions. Additionally, the authors reported on the assessment of the underlying logic model or theoretical underpinnings of what the authors will term the "Habitat Model." Design/methodology/approach – This study utilized a one-shot case study design to obtain data. In a one-shot case study the experimental group is exposed to the independent variable (X), then observations of the dependent variable (O) were made. No observations were made before the independent variable was introduced. A one-shot case study design was necessary as this is the first impact study conducted by BAHFH because of the changes within BAHFH over the years as well as the lack of consistent archival data on families and operations. Findings – Most of the feedback obtained from stakeholders was positive. Many of the demographic variables showed significant improvement in partner family life style since moving into a Habitat house. Practical implications – The findings of this study provide evidence of positive economic, social, and psychological impacts on families participating in BAHFH homeownership and on their communities. It also showed substantial economic impacts on the communities served. Furthermore, this study showed that other stakeholders in the process were substantially and positively impacted. Finally, this study pointed to a number of things that BAHFH needed to change such as homeowner education, financial counseling, and the opening of a local ReStore. Originality/value – The current study provides data that provide evidence of positive economic, social, and psychological impacts on families participating in BAHFH homeownership opportunities.